2017
DOI: 10.1177/1550147717705240
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanically influenced mobile and participatory pedestrian data for bridge monitoring

Abstract: Future structural health monitoring systems are evolving toward crowdsourced, autonomous, sustainable forms based on which damage-indicative structural features can be identified. Unlike conventional sensor systems, they serve as nonstationary, mobile, and distributed sensor network components. For example, smartphone sensors carried by pedestrians decouple from the structure of interest, making it difficult to measure structural vibration. Taking bridges as instances, smartphone sensor data contain not only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…Previously, it has been shown that actual crowdsourcing results (results from uncontrolled citizens) matched well with the reference identification results [32]. These uncertainties are extensively studied in [48] including spatiotemporal variation of a citizen sensor [33], phone orientation which is subjected to change before, during, and after the measurements [34], and biomechanical distortions caused by human nature [50]. Therefore, in this paper, the main focus is on uncertainties induced by ground motions and FE model parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it has been shown that actual crowdsourcing results (results from uncontrolled citizens) matched well with the reference identification results [32]. These uncertainties are extensively studied in [48] including spatiotemporal variation of a citizen sensor [33], phone orientation which is subjected to change before, during, and after the measurements [34], and biomechanical distortions caused by human nature [50]. Therefore, in this paper, the main focus is on uncertainties induced by ground motions and FE model parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Since there is a buffer zone in our position judgment, the positioning accuracy almost meets the demand. But when it comes to mass usage, embedded Geofencing tools in IOS or Android, which can provide a more accurate location by fusing multiple positioning approaches [63], would be a better choice. For other sensors, the accuracy is affected by sensor heterogeneity and pedestrian biomechanical effects.…”
Section: ) Accuracy Limitationsmentioning
confidence: 99%
“…In fact, a number of studies have shown the feasibility of smartphone accelerometer applications with civil infrastructure examples. [6][7][8][9][10][11][12][13][14][15][16] One significant challenge, however, is whether these systems can be used for very low frequency structures such as long-span bridges. In addition to the measurement limitations of smartphone-embedded MEMS accelerometers for very low frequency motion, smartphone sensors and mobile applications, by default, are embedded with high pass filters.…”
Section: Introductionmentioning
confidence: 99%